IMPLEMENTATION OF BASED HUMAN RESOURCE MANAGEMENT ISLAMIC VALUES - Sholihun, M.; Jamilah, Siti (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
This study aims to determine the application of Islamic values to every activity in human resource management, especially at BMT Al Hijrah KAN Jabung Syariah. This research is a field research with research subjects BMT Al-Hijrah KAN Jabung Syariah. The technique of selecting respondents using purposive sampling technique. The results showed that the management system at BMT Al-Hijrah KAN Jabung Syariah was in line with the daily operational system of the Muslim community in general. Values Islam is divided into categories consisting of faith, sharia, and morals. The suggested implications for improving the quality of HR, BMT Al-Hijrah KAN Jabung Syariah need to maintain professionalism criteria along with the application of Islamic values so that the quality of the company is maintained. In addition, it was found that achievement-based compensation factors in HR management can also be applied together with Islamic values at BMT Al-Hijraj KAN Jabung Syariah. This is because compensation is related to faith, sharia, and morals. Therefore, it is suggested that BMT Al-Hijrah KAN Jabung Syariah needs to improve regulations regarding compensation based on Islamic values so that HR management can maintain professionalism through achievement while implementing Islamic values.